Serum Lipemik dengan Flokulan Gamma-Siklodekstrin pada Pemeriksaan Glukosa - Alde Fajar Pambudi; Subrata Tri Widada; Budi Setiawan (Medical Laboratory Technology Journal, 2017)
Lipemic serum caused by lipoprotein particles such as chylomicrons, VLDL (Very Low-Density Lipoprotein) and triglycerides. This situation causes interference chromophoric photometric analysis, interference on the wavelength and light scattering caused by the presence of lipid particles. This study aims to determine and differences glucose levels in lipemic serum with and without the addition of gamma-cyclodextrin incubation temperature 23oC. The study's pre-experimental use research design static group comparison. The samples were all lipemic serum many as 20 samples. The research findings were the glucose levels without adding the flocculant Gamma-cyclodextrin incubation temperature 23oC was 267,19 mg/dl. Whereas the glucose levels with adding the flocculant Gamma-cyclodextrin incubation temperature 23oC was 169,23 mg/dl. The difference of glucose levels with or without adding the flocculant Gamma-cyclodextrin incubation temperature 23oC was 97,96 mg/dl(35,23%).